A method for preparing a graphite felt electrode material loaded with bimetallic particles by reduction method

By preparing loaded bimetallic particles on the surface of graphite felt electrode material, the problems of severe hydrogen evolution reaction and low Cr3+/Cr2+ activity in the iron-chromium flow battery electrode material are solved, and high energy efficiency battery performance is achieved.

CN118099459BActive Publication Date: 2025-03-18BEIJING UNIV OF CHEM TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410168280.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-06
Publication Date
2025-03-18
Estimated Expiration
2044-02-06

AI Technical Summary

Technical Problem

The existing iron-chromium flow battery electrode materials have problems such as severe negative electrode hydrogen evolution reaction and low Cr3+/Cr2+ activity, resulting in low energy efficiency.

Method used

The reduction method is used to prepare bimetallic particles on the surface of graphite felt electrode material, and the redox reaction activity is improved through high-ultra-potential metal ions and alleviate the analytical hydrogen reaction.

Benefits of technology

The long-term circulation energy efficiency and rate circulation energy efficiency of iron-chromium flow batteries have been improved, and the ratio circulation energy efficiency is stable between 83.0% and 85.2%, up to 85.2%, and the ratio circulation energy efficiency can reach 86.6%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004700310640000011
    Figure HDA0004700310640000011
  • Figure HDA0004700310640000012
    Figure HDA0004700310640000012
  • Figure HDA0004700310640000021
    Figure HDA0004700310640000021
Patent Text Reader

Abstract

A method for preparing a graphite felt electrode material loaded with bimetallic particles by a reduction method is particularly applicable to the field of iron-chromium flow battery electrodes. The composite electrode material reduces metal ions adsorbed on the graphite felt into metal particles by a reduction method, thereby obtaining an electrode material loaded with bimetallic particles. First, a uniformly dispersed solution containing bimetallic ions is prepared, and the graphite felt that has been cleaned and pretreated is immersed in it. After the bimetallic ions are uniformly loaded, an appropriate amount of sodium borohydride (NaBH 4 ) solution, causing a reduction reaction with metal ions, and after the reaction is complete, a new graphite felt electrode material loaded with bimetallic particles is obtained. The composite electrode material of the present invention can improve the activity of the redox reaction, slow down the dehydrogenation reaction, and achieve high energy efficiency of the liquid flow battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrode materials for iron-chromium liquid flow batteries, and in particular to a method for preparing a novel graphite felt electrode material loaded with bimetallic particles by a reduction method. The material is suitable for iron-chromium liquid flow batteries. Background Art

[0002] Global warming and climate change can lead to negative impacts such as rising temperatures, extreme weather events and rising sea levels, which will not only affect our lives, but also have serious impacts on the ecosystem. Sustainable development involves not only environmental protection, but also economic development. With the development of renewable energy such as solar energy, wind energy and hydropower, energy storage technology has become an important supplement to these energy sources. The amount of electricity generated by renewable energy is unstable, and energy storage technology can effectively store this energy to ensure the stable operation of the power grid. The intelligentization of the power grid requires a large number of energy storage devices, such as battery energy storage systems and power energy storage systems, to achieve real-time dispatch and optimized operation of the power grid.

[0003] The electrodes of the iron-chromium flow battery are the sites where the iron ions and chromium ions in the electrolyte react chemically to achieve the storage and release of electrical energy. 2+ Will react with Cr in the electrolyte 3+ Reaction to form Cr 2+ and Fe 3+ , this process generates electrons, which in turn generates an electric current, storing electrical energy in the battery. During discharge, electrons flow out of the battery, Cr 2+ and Fe 3+ Reaction to form Cr 3+ and Fe 2+ , this process will generate voltage, thereby releasing the electrical energy stored in the battery. Electrode modification is the main method to improve the performance of iron-chromium flow batteries, and it is also an important research direction for scientists. Electrode modification is mainly carried out through the following methods: changing the physical or chemical properties of electrode materials, for example, changing the layered structure of the electrode surface, changing the surface activity of the electrode, etc., adding carbon-based catalysts, metal catalysts, composite catalysts, etc. to the electrode surface to improve the electrochemical properties of iron-chromium flow battery electrodes, thereby improving battery performance.

[0004] Here, we use the reduction method to reduce the metal ions impregnated and adsorbed on the surface of graphite felt fibers into metal particles, and use the metal ions with high overpotential on the electrode surface to increase the activity of the redox reaction and slow down the dehydrogenation reaction. The energy efficiency of the iron-chromium flow battery assembled with this composite electrode material can be stabilized between 83.0% and 85.2% for a long time cycle, and can reach up to 85.2%, and its rate cycle energy efficiency can reach up to 86.6%. Summary of the invention

[0005] The present invention aims to overcome the shortcomings of existing iron-chromium liquid flow battery electrode materials, provide a method for synthesizing electrode materials, prepare a new type of graphite felt electrode material loaded with bimetallic particles by reduction method, solve the current problems of serious negative electrode hydrogen evolution reaction and Cr 3+ / Cr 2+ The electrode material prepared by this method can achieve high energy efficiency of liquid flow battery.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing a graphite felt electrode material loaded with bimetallic particles by a reduction method, characterized by the following steps and process conditions:

[0008] Step 1) Cut the graphite felt electrode material into size (e.g. 3 × 3 cm 2 ), then use organic solvents such as acetone, ethanol, etc. to ultrasonically clean the graphite felt to remove organic and inorganic impurities contained in the graphite felt, then use deionized water to ultrasonically clean it to remove the organic solvent contained, and finally dehydrate and vacuum dry it;

[0009] Step 2) placing the graphite felt in step 1) into a tubular furnace and performing heat pretreatment at a certain temperature;

[0010] Step 3) Weigh a certain amount of two metal salts and put them into a container, add an appropriate amount of ethylene glycol solvent and stir, and after they are completely dissolved, immerse the graphite felt prepared in step 2) and put them into a constant temperature oscillator to oscillate at room temperature for a period of time to obtain a graphite felt uniformly loaded with metal ions;

[0011] Step 4) Weigh a certain amount of NaBH4 and add an appropriate amount of ethylene glycol solvent, and after it is completely dissolved, obtain a NaBH4 solution of a certain concentration;

[0012] Step 5) Adding the NaBH4 solution obtained in step 4) into the container of step 3) to allow the reduction reaction to proceed completely, and then continue to place the container in a constant temperature oscillator and oscillate at room temperature to obtain a graphite felt material loaded with two metal particles;

[0013] Step 6) The graphite felt electrode material loaded with bimetallic particles obtained in step 5) is washed with deionized water, and after washing, is moved to a vacuum drying oven and heated and dried at a certain temperature;

[0014] Step 7) The graphite felt obtained in step 6) is then placed in a quartz tube and calcined in a tube furnace. After the calcination is completed, a new type of graphite felt electrode material loaded with bimetallic particles is obtained.

[0015] According to the above preparation method, its specific process parameters are as follows:

[0016] 1) The cleaning method in the above step 1) is to soak in acetone and ethanol solution for 1 hour, ultrasonicate for 1 hour, then soak in deionized water for 1 hour, and ultrasonicate for 1 hour.

[0017] 2) In the above step 2), the heat treatment temperature is 300 ~ 700 °C, the holding time is 4 ~ 6 h, and the heating rate is 0 ~ 10 °C / min, corresponding to air conditions;

[0018] 3) In the above step 3), the type of the added metal salt is different, and the above metal salt includes but is not limited to compounds with high overpotential metal ions such as ZnCl2, BiCl3, SnCl2, and PbCl2;

[0019] Step 3) Every 9 cm 2 The graphite felt corresponds to 0.05 ~ 5 g total metal salt, 10 ~ 50 mL ethylene glycol solution corresponds to 0.5 ~ 4.0 g NaBH4, 10 ~ 50 mL ethylene glycol solution in step 4; preferably, the mass ratio of the two metal salts is 1:2-2:1.

[0020] Step 3) Constant temperature oscillation time is 10 to 60 min;

[0021] 5) In the above step 5), the mixture is placed in a constant temperature oscillating box for reaction, and the oscillation time is 0 to 60 min;

[0022] 6) The graphite felt rinsed in step 6 above is dried in a vacuum drying oven at 80-120°C for 24 h;

[0023] 7) The graphite felt in the above step 7) is first heated to 100 ~ 300 °C under N2 atmosphere, with a holding time of 0.5 ~ 3 h and a heating rate of 5 ~ 20 °C / min, and then continued to be heated to 600 ~ 1000 °C, with a holding time of 0.5 ~ 3 h and a heating rate of 5 ~ 10 °C / min.

[0024] The above-mentioned electrode material preparation method is applied as a negative electrode in the field of iron-chromium liquid flow batteries.

[0025] Compared with the prior art, the present invention has the following significant advantages and beneficial effects:

[0026] 1. The present invention uses commercial-scale graphite felt, ethylene glycol solvent, NaBH4, metal salts and the like as raw materials, and adopts a reduction method to prepare a new type of graphite felt electrode material loaded with bimetallic particles, which solves the current problems of severe negative electrode hydrogen evolution reaction and Cr 3+ / Cr 2+ Problems such as low activity.

[0027] 2. The process steps of the present invention are suitable for large-scale and commercial production, the method is simple, the cost is low, and the operation is easy, which is conducive to the large-scale application of iron-chromium liquid flow batteries.

[0028] 3. The key to the present invention is that the metal ions used have a high hydrogen evolution overpotential. The metal ions adsorbed on the carbon fibers are reduced to metal particles by NaBH4 reduction. This catalyst greatly increases the active sites, thereby reducing the occurrence of negative electrode hydrogen evolution reaction and improving the activity of the composite electrode material.

[0029] In summary, the present invention uses graphite felt produced on a commercial scale as a carrier, and uses ethylene glycol, NaBH4, metal salts, etc. as raw materials. By means of metal reduction, a uniform ethylene glycol solution containing metal salts is first prepared, and then immersed in the heat-treated graphite felt. After the metal ions are completely adsorbed on the graphite felt, a certain concentration of NaBH4 solution with ethylene glycol as a solvent is added for reduction reaction, thereby obtaining a new type of graphite felt electrode material for loading bimetallic particles prepared by a reduction method. This method is expected to prepare a commercial electrode for an iron-chromium flow battery with high energy efficiency. The composite electrode material of the present invention can improve the activity of the redox reaction and slow down the dehydrogenation reaction. The energy efficiency of the iron-chromium flow battery assembled by the composite electrode material for long-term circulation can be stabilized between 83.0% and 85.2%, and can reach up to about 85.2%, and its rate cycle energy efficiency can reach up to 86.6%. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Cyclic voltammetry test diagram of the bimetallic catalyst loaded graphite felt electrode material prepared in Example 1 and blank graphite felt

[0031] Figure 2 The efficiency and corresponding charge and discharge capacity of the bimetallic catalyst-loaded graphite felt electrode material prepared in Example 1 after 100 cycles

[0032] Figure 3 Efficiency diagram of the rate cycle of the bimetallic catalyst-loaded graphite felt electrode material prepared in Example 1

[0033] Figure 4 The charge and discharge curve of the bimetallic catalyst-loaded graphite felt electrode material prepared in Example 1

[0034] Figure 5 The efficiency diagram of the rate cycle of the bimetallic catalyst loaded graphite felt electrode material prepared by Example 1, Example 2, Example 3 and blank graphite felt

[0035] Figure 6 XRD diagram of the bimetallic catalyst loaded graphite felt electrode material prepared in Example 1 and blank graphite felt DETAILED DESCRIPTION

[0036] The present invention is described in detail below through specific examples, but the use and purpose of these exemplary embodiments are only used to illustrate the present invention, and do not constitute any form of limitation on the actual protection scope of the present invention, nor limit the protection scope of the present invention to these. Example

[0037] Cut the graphite felt into 3 × 3 cm 2 The cut graphite felt was cut into sizes, and the cut graphite felt was soaked in acetone and ethanol and treated with ultrasound for 1 h respectively to remove various organic and inorganic impurities contained in the graphite felt. Then it was soaked in deionized water and treated with ultrasound for 2 h to remove the organic solvent contained in it. Then it was dehydrated and vacuum dried. The dried graphite felt was placed in a tubular furnace for heat pretreatment. The heat pretreatment temperature was 500 ℃, the heating time was 5 h, and the heating rate was 5 ℃ / min.

[0038] Weigh 1.0 g of BiCl3 and 2.0 g of SnCl2, add 30 mL of ethylene glycol and stir until completely dissolved, immerse the pretreated graphite felt material, put it in a constant temperature oscillating box and oscillate it at room temperature for a period of time until the solution is clear; weigh 3.0 g of NaBH4, add 30 mL of ethylene glycol and stir until completely dissolved; add the prepared NaBH4 solution to the beaker of the graphite felt material fully loaded with metal ions to react, and after the reaction is completely completed, continue to put it in a constant temperature oscillating box and oscillate it at room temperature for a period of time; after the oscillation is completed, wash the obtained graphite felt material with deionized water, put it in a vacuum drying oven for drying, the drying temperature is 100 ℃, and the drying time is 24 h; finally, put the dried graphite felt material into a tubular furnace for staged calcination, first keep it at 150 ℃ for 1 h, the heating rate is 10 ℃ / min, and then keep it at 650 ℃ for 2 h, the heating rate is 5 ℃ / min, and finally a new graphite felt electrode material with bimetallic particles uniformly loaded by impregnation was obtained.

[0039] The bimetallic particle loaded graphite felt electrode material prepared in Example 1 and a blank graphite felt material were subjected to cyclic voltammetry test, and the test results are as follows: Figure 1 As shown, the traditional three-electrode system was used to evaluate the electrocatalytic performance of the electrode materials.

[0040] Depend on Figure 1 It can be seen that the bimetallic particle-uniformly loaded graphite felt electrode material prepared by impregnation in Example 1 of the present invention exhibits excellent electrocatalytic performance. The curve of the electrode material of Example 1 has a pair of clear redox peaks compared with the curve of the blank graphite felt, wherein the oxidation peak matches equation (1) and the reduction peak corresponds to equation (2).

[0041] Cr 2+ − e − ↔ Cr 3+ (1)

[0042] Cr 3+ + e − ↔ Cr 2+ (2)

[0043] Oxidation and reduction peak currents are used to describe electrochemical performance. Figure 1 It can be seen that under the same test conditions, the absolute values ​​of the oxidation peak and reduction peak current of the material in Example 1 are higher than those of the blank graphite felt; compared with the blank graphite felt, Example 1 has an obvious reduction peak, indicating that the loaded bimetallic particle electrode material prepared in Example 1 has better redox reversibility and higher electrochemical activity, further reflecting that this material has higher electrocatalytic activity.

[0044] The loaded bimetallic particle electrode material prepared in Example 1 was used as the negative electrode to assemble a single cell (the electrolyte composition was 1 M FeCl2, 1 M CrCl3, 3 M HCl; the positive electrode material was a graphite felt material obtained by washing, drying, and heat pretreatment at 500 °C for 5 h; the same as in the following examples) and the negative electrode was used in an iron-chromium flow battery at 60 mA cm −2 The cycle test was carried out at a current density of . After 100 charge and discharge cycles, the efficiency results are as follows Figure 2 As shown, after cycling at different current densities, the efficiency results are as follows Figure 3 As shown, the first cycle charge and discharge curve is as follows Figure 4 As shown. Figure 2 It can be seen that the average coulombic efficiency (CE) is greater than 95% and the energy efficiency (EE) is greater than 83%, showing excellent battery performance. Figure 3 It can be seen that after the rate cycle, the EE of Example 1 can still reach the level before the rate cycle. Example

[0045] Cut the graphite felt into 3 × 3 cm 2The cut graphite felt was cut into sizes, and the cut graphite felt was soaked in acetone and ethanol and treated with ultrasound for 1 h respectively to remove various organic and inorganic impurities contained in the graphite felt. Then it was soaked in deionized water and treated with ultrasound for 2 h to remove the organic solvent contained in it. Then it was dehydrated and vacuum dried. The dried graphite felt was placed in a tubular furnace for heat pretreatment. The heat pretreatment temperature was 500 ℃, the heating time was 5 h, and the heating rate was 5 ℃ / min.

[0046] Weigh 2.0 g of BiCl3 and 1.0 g of SnCl2, add 30 mL of ethylene glycol and stir until completely dissolved, immerse the pretreated graphite felt material, put it in a constant temperature oscillating box and oscillate it at room temperature for a period of time until the solution is clear; weigh 3.0 g of NaBH4, add 30 mL of ethylene glycol and stir until completely dissolved; add the prepared NaBH4 solution to the beaker of the graphite felt material fully loaded with metal ions to react, and after the reaction is completely completed, continue to put it in a constant temperature oscillating box and oscillate it at room temperature for a period of time; after the oscillation is completed, wash the obtained graphite felt material with deionized water, put it in a vacuum drying oven for drying, the drying temperature is 100 ℃, and the drying time is 24 h; finally, put the dried graphite felt material into a tubular furnace for staged calcination, first keep it at 150 ℃ for 1 h, the heating rate is 10 ℃ / min, and then keep it at 650 ℃ for 2 h, the heating rate is 5 ℃ / min, and finally a new graphite felt electrode material with bimetallic particles uniformly loaded by impregnation was obtained.

[0047] The bimetallic granular graphite felt electrode material prepared in Example 2 was used as the negative electrode to assemble a single cell, and a rate cycle test was performed at different current densities in an iron-chromium liquid flow battery. The results are as follows: Figure 5 After adjusting the metal salt content, the energy efficiency of the battery dropped significantly, but the coulombic efficiency did not decrease significantly, proving the reliability of this method. Example

[0048] Cut the graphite felt into 3 × 3 cm 2 The cut graphite felt was cut into sizes, and the cut graphite felt was soaked in acetone and ethanol and treated with ultrasound for 1 h respectively to remove various organic and inorganic impurities contained in the graphite felt. Then it was soaked in deionized water and treated with ultrasound for 2 h to remove the organic solvent contained in it. Then it was dehydrated and vacuum dried. The dried graphite felt was placed in a tubular furnace for heat pretreatment. The heat pretreatment temperature was 500 ℃, the heating time was 5 h, and the heating rate was 5 ℃ / min.

[0049] Weigh 2.0 g of BiCl3 and 2.0 g of SnCl2, add 30 mL of ethylene glycol and stir until completely dissolved, immerse the pretreated graphite felt material, put it in a constant temperature oscillating box and oscillate it at room temperature for a period of time until the solution is clear; weigh 3.0 g of NaBH4, add 30 mL of ethylene glycol and stir until completely dissolved; add the prepared NaBH4 solution to the beaker of the graphite felt material fully loaded with metal ions to react, and after the reaction is completely completed, continue to put it in a constant temperature oscillating box and oscillate it at room temperature for a period of time; after the oscillation is completed, wash the obtained graphite felt material with deionized water, put it in a vacuum drying oven for drying, the drying temperature is 100 ℃, and the drying time is 24 h; finally, put the dried graphite felt material into a tubular furnace for staged calcination, first keep it at 150 ℃ for 1 h, the heating rate is 10 ℃ / min, and then keep it at 650 ℃ for 2 h, the heating rate is 5 ℃ / min, and finally a new graphite felt electrode material with bimetallic particles uniformly loaded by impregnation was obtained.

[0050] The bimetallic particle electrode material prepared in Example 3 was used as the negative electrode to assemble into a single cell, and a rate cycle test was performed at different current densities in an iron-chromium liquid flow battery. The results are shown in FIG. Figure 5 After adjusting the content of metal salt, the energy efficiency of the battery decreased significantly, but the coulombic efficiency did not decrease significantly, which proved the reliability of this method.

Claims

1. A method for preparing a graphite felt electrode material loaded with bimetallic particles by a reduction method, characterized in that: The process includes the following steps and process conditions: Step 1) First, the graphite felt electrode material is cut into size, and then the graphite felt is ultrasonically cleaned with acetone and ethanol to remove organic and inorganic impurities contained in the graphite felt, and then ultrasonically cleaned with deionized water to remove the organic solvent contained, and finally dewatered and vacuum dried; Step 2) placing the graphite felt in step 1) into a tubular furnace and performing heat pretreatment at a certain temperature; Step 3) Weigh two metal salts and put them into a container, add ethylene glycol solvent and stir, and after they are completely dissolved, immerse them in the graphite felt prepared in step 2), put them into a constant temperature oscillator and oscillate them at room temperature for 10 to 60 minutes to obtain a graphite felt uniformly loaded with metal ions; the types of the added metal salts are different, and the above metal salts are selected from ZnCl2, BiCl3, SnCl2, and PbCl2, and the mass ratio of the two metal salts is 1:2-2:1; wherein each 9 cm 2 The graphite felt corresponds to 0.05 ~ 5 g total metal salt and 10 ~ 50 mL ethylene glycol; Step 4) Weigh NaBH4 and add it to ethylene glycol solvent, and after it is completely dissolved, obtain a NaBH4 solution; wherein 0.5 to 4.0 g NaBH4 corresponds to 10 to 50 mL ethylene glycol; Step 5) Adding the NaBH4 solution obtained in step 4) into the container of step 3) to allow the reduction reaction to proceed completely, and then continue to place the container in a constant temperature oscillator and oscillate at room temperature to obtain a graphite felt material loaded with two metal particles; Step 6) The graphite felt electrode material loaded with bimetallic particles obtained in step 5) is washed with deionized water, and after washing, is moved to a vacuum drying oven for heating and drying; Step 7) Subsequently, the graphite felt obtained in step 6) is placed in a quartz tube and calcined in a tube furnace in stages. After the calcination is completed, a graphite felt electrode material loaded with bimetallic particles is obtained; In step 2), the heat treatment temperature is 300 ~ 700 °C, the holding time is 4 ~ 6 h, and the heating rate is 0 ~ 10 °C / min and is not 0; the corresponding condition is air condition.

2. The method according to claim 1, characterized in that The cleaning method in step 1) is to soak in acetone and ethanol solutions for 1 hour, ultrasonicate for 1 hour, and then soak in deionized water for 1 hour and ultrasonicate for 1 hour.

3. The method according to claim 1, characterized in that In step 5), it is placed in a constant temperature oscillating box for reaction, and the oscillation time is 0 to 60 min and is not 0.

4. The method according to claim 1, characterized in that The graphite felt rinsed in step 6) is dried in a vacuum drying oven at 80-120°C for 24 h.

5. The method according to claim 1, characterized in that In step 7), the graphite felt is first heated to 100-300°C under N2 atmosphere protection, with a holding time of 0.5-3 h and a heating rate of 5-20°C / min, and then continued to be heated to 600-1000°C, with a holding time of 0.5-3 h and a heating rate of 5-10°C / min.

6. A graphite felt electrode material prepared according to the method according to any one of claims 1 to 5.

7. Application of the graphite felt electrode material prepared by the method according to any one of claims 1 to 5, directly used as a negative electrode in the field of iron-chromium liquid flow batteries.

Citation Information

Patent Citations

  • Iron-chromium redox flow battery electrode material and preparation method thereof

    CN114744223A

  • Preparation method of graphite felt modified electrode for all-vanadium redox flow battery

    CN115863666A

  • Graphite felt negative electrode of iron-chromium flow battery and modification method of graphite felt negative electrode

    CN117080462A